1995
DOI: 10.1021/bi00013a042
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Interactions Stabilize Long Range Loops in the Initial Folding Intermediates of Reduced Bovine Pancreatic Trypsin Inhibitor

Abstract: A search for the topology of the chain folding of reduced bovine pancreatic trypsin inhibitor (BPTI), in unfolded and partially folded states, was done by means of time resolved dynamic nonradiative excitation energy transfer (ET) measurements. Four double labeled BPTI derivatives were used in which the donor was attached to the N-terminal arginine residue and the acceptor was specifically attached to one of the lysine residues. The four derivatives form a series of labeled backbone segments of increasing leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 79 publications
8
75
0
Order By: Relevance
“…2) (Ittah and Haas 1995). We hypothesized that the earliest steps in the folding transition are the closure of few long loop (25-35 residues) segments by NLIs between clusters with mostly non-polar residues at their ends (Ittah and Haas 1995;Haas 2005).…”
Section: The Loop Hypothesismentioning
confidence: 99%
“…2) (Ittah and Haas 1995). We hypothesized that the earliest steps in the folding transition are the closure of few long loop (25-35 residues) segments by NLIs between clusters with mostly non-polar residues at their ends (Ittah and Haas 1995;Haas 2005).…”
Section: The Loop Hypothesismentioning
confidence: 99%
“…In this respect, it will be instructive to investigate how our predictions might be modulated by the application of other tractable explicitchain models that incorporate nonnative interactions (40,60), interaction heterogeneity (12,61,62), and/or side-chain effects (13) and ascertain whether a similar trend exists in all-atom simulations (63). Experiments revealed that some proteins do fold by first forming nonlocal contacts (64,65). It will be extremely illuminating if differences in contact pattern between TPs and the non-TP population in the unfolded basin can be quantified by future single-molecule experiments.…”
Section: Initial Stages Of Transition Paths Have Statistically Atypicmentioning
confidence: 99%
“…A quite different view of the dimensions of reduced BPTI has emerged from studies in which energy transfer measurements were used to analyze the distributions of distances between fluorescent probes attached to different sites along the polypeptide~Amir & Haas, 1988;Amir et al, 1992;Ittah & Haas, 1995!. The results of these studies indicate the presence of distinct subpopulations of molecules with different distributions of intramolecular distances. The average distances calculated for the more compact subpopulation are nearly as small as those predicted for the native protein.…”
Section: The Nature and Role Of Nonrandom Structure In Fully Reduced mentioning
confidence: 99%